Bourdieu, Religion and Pluralistic Societies - Kühle, Lene (Bulletin for the study of religion, 2012)
It is widely recognised that the theory of practise of French sociologist Pierre Bourdieu may provide insights for the study of religion due to its general importance for social sciences and humanities in general. When it comes to Bourdieu's specific work on religion and in particular his concept of the religious field, scholars have been less enthusiastic in particular in relation to religion in complex societies. This article argues however that Bourdieu's work on the religious field may have been rejected prematurely, and that it may provide a frutile point of departure for studies of religion in pluralistic societies.